EDUCATING FOR VALUE REORIENTATION IN DEMONSTRATION SECONDARY SCHOOLS IN KADUNA STATE, NIGERIA - Ngozi EZEMA-KALU (Scholars Digest Publishing, 2025)
This study investigated on educating for value reorientation in demonstration secondary schools in Kaduna State, Nigeria. The objective of the study include: To determine the role teachers, play in facilitating value reorientation among students in demonstration secondary schools and To identify the challenges faced by demonstration secondary schools in Kaduna State in implementing value reorientation initiatives. Quantitative research methodology was adopted for this study. The survey research design was used for this study. The population for this study consists of seventy (70) teachers of Demonstration Secondary School. Census sampling technique was used for this study, where all seventy (70) teachers of Demonstration Secondary School were used as respondents. A closed-ended questionnaire was used for data collection. The instrument was validated by the researcher’s supervisors using face and content validity. The researcher collects an introductory letter from the Department to enable the collection of data. One (1) research assistant will be employed. Descriptive statistics was used to analyze the data collected from the research questions. Frequency count and percentage was used to analyze research question and the benchmark is 50% and above. The study finds out that the role teachers, play in facilitating value reorientation among students in demonstration secondary schools are Enforcing rules and codes of conduct to instill discipline and responsibility, Encouraging open discussions about values, ethics, and societal norms among others. The study also discovered that Peer Influence, Resistance to Change from Students and Staff and Social Media Influence on Student Behavior are the challenges faced by demonstration secondary schools in Kaduna State in implementing value reorientation initiatives.
Keywords: Educating; Reorientation; Value.